International Students at the Intersection of Local Policy and Global Emergency (Comparative & International Education Series, 2021)
Exploring the cultural political economy (CPE) of countries facilitates examination of the discourses and institutions informing the development of locally situated international student mobility (ISM) policies which bound the international student experience. The central aim of this research is to examine the ways in which national ISM policy responses to emergencies are tied to many of the same emphases and imperatives that guide original national ISM policy development in less fraught times. This study therefore introduces a collection of national ISM policies, discourses, and issues and subsequent adjustments to them in the course of national responses in Canada and the United States during the first six months of the COVID-19 pandemic. I conclude with suggestions for future research in this vein, especially as it relates to ISM policy responses to global emergencies.